2019
DOI: 10.5658/wood.2019.47.1.8
|View full text |Cite
|
Sign up to set email alerts
|

Pore Characterization in Cross Section of Yellow Poplar (Liriodendron tulipifera) Wood

Abstract: This study was conducted to analyze the pore structure of Yellow poplar. Cross-sectional surfaces of heartwood and sapwood of Yellow poplar (Liriodendron tulipifera) were observed by SEM, and the true density of the heartwood, intermediate wood and sapwood were measured by gas pycnometery, while gas permeability and pore size of heartwood, intermediate wood and sapwood were measured by capillary flow porometery. The pores were classified as through pore, blind pore and closed pore.It was determined that the pe… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

1
6
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 19 publications
(7 citation statements)
references
References 10 publications
1
6
0
Order By: Relevance
“…Pore size was measured by capillary flow porometry [32][33][34] using the standard method of ASTM F-316 [35]. This method's main characteristic is that it measures the constricted segments of only the through-pores to measure only the pores that affect permeability [25,31,[34][35][36][37][38][39]. The same equipment used for gas permeability was used to measure pore size.…”
Section: Pore Size Analysismentioning
confidence: 99%
“…Pore size was measured by capillary flow porometry [32][33][34] using the standard method of ASTM F-316 [35]. This method's main characteristic is that it measures the constricted segments of only the through-pores to measure only the pores that affect permeability [25,31,[34][35][36][37][38][39]. The same equipment used for gas permeability was used to measure pore size.…”
Section: Pore Size Analysismentioning
confidence: 99%
“…Closed pores are formed in the middle of the membranes without access to out layers, which have no contribution to diffusion or partition of chemicals into the membranes. 15 Our recent study of diffusion of large molecules through nanofibrous membranes found that only when the measured pore size of the membrane is close to 1000 times larger than diffusant molecules, a regular diffusion pattern of the molecules could be observed through the membrane. 16 Such results indicate that the measured pore sizes could not represent the real pores of the nanofibrous membranes contributing to the diffusion of large molecules, which is defined as effective pores of the membranes.…”
mentioning
confidence: 98%
“…The through pores can allow particles to penetrate through the membrane, and the blind pores have closed ends that can block the diffusion of the particles. Closed pores are formed in the middle of the membranes without access to out layers, which have no contribution to diffusion or partition of chemicals into the membranes . Our recent study of diffusion of large molecules through nanofibrous membranes found that only when the measured pore size of the membrane is close to 1000 times larger than diffusant molecules, a regular diffusion pattern of the molecules could be observed through the membrane .…”
mentioning
confidence: 99%
See 2 more Smart Citations